2019
DOI: 10.15560/15.3.455
|View full text |Cite
|
Sign up to set email alerts
|

Silent pirates: Anolis sagrei Duméril & Bibron, 1837 (Squamata, Dactyloidae) taking over Panama City, Panama

Abstract: Anolis sagrei Duméril & Bibron, 1837 is one of the most widespread reptiles in the world, having colonized more than 15 countries on 2 continents. It inhabits open areas and is commonly found around big cities. We noticed the presence of an unreported, nonnative population in Panama City, Panama, which has been established since at least 5 years. We report Anolis sagrei for the first time in Panama based on collected specimens. We argue that the species is currently abundant in some areas and it could be a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Although it first arose on Cuba, the species now has the largest native range of any anole with natural diaspora populations found across islands of the northern Caribbean as well as coastal areas of Mesoamerica 21,22 . It is also a prolific invader with non-native populations established on many additional islands in the West Indies 23,24 , Costa Rica, multiple locations in both North 25 and South America 26,27 , as well as remote islands of the central Atlantic Ocean 28,29 , Hawaii 30 , Taiwan, and mainland Asia, Europe, and the Middle East. A recent analysis of genome-scale sequence data revealed that A. sagrei evolved on Cuba toward the end of the Miocene 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Although it first arose on Cuba, the species now has the largest native range of any anole with natural diaspora populations found across islands of the northern Caribbean as well as coastal areas of Mesoamerica 21,22 . It is also a prolific invader with non-native populations established on many additional islands in the West Indies 23,24 , Costa Rica, multiple locations in both North 25 and South America 26,27 , as well as remote islands of the central Atlantic Ocean 28,29 , Hawaii 30 , Taiwan, and mainland Asia, Europe, and the Middle East. A recent analysis of genome-scale sequence data revealed that A. sagrei evolved on Cuba toward the end of the Miocene 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Hemidactylus frenatus is also a possible predator of G. albogularis since it attacks, predates, and consumes the eggs of other lizards, causing interspecific predation (Cole et al, 2005;Díaz Pérez et al, 2012;Gardner & Jasper, 2012), as in the case of G. albogularis, where attacks by H. frenatus have been evidenced (Alemán & Sunyer, 2015) and in the case of N. sagrei, which is known for its cannibalistic behavior and for predating other lizards (Campbell & Gerber, 1996;Gerber, 1999;Lee, 2000;Nicholson et al, 2000;Norval, 2007;Norval et al, 2010). Batista et al (2019) mentioned the capacity that this anole might have in displacing G. albogularis (Williams, 1969;Schoener et al, 2017). We discuss these behaviors as might be very similar to those mentioned by Pianka (1973) and Fisher et al (2019) that lead to competition between invasive and native species.…”
mentioning
confidence: 51%
“…An introduced population also exists in the vicinity of Limón, Costa Rica (Savage and Bolaños-Vives 2005). Batista et al (2019) reported established populations of N. sagrei at several sites within and around Panama City. They also mentioned that those populations might have become established approximately five years ago, and arrived there as released pets, or more probably, from shipments arriving at the port of Balboa (Table 2, Map 11).…”
Section: Norops Sagrei (Duméril and Bibron 1837)mentioning
confidence: 99%